The Effect of Co-rearing with Females on the Quantity and Quality of Mouse (Mus Musculus) Spermatozoa - Evi Hanizar; Titiek Fianti; Dwi Nur Rikhma Sari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Coexistence with the same sex is often discussed in recent times, but its effect on reproductive health has not been widely publicized. This study used male (Mus musculus) animals to determine the effect of co- rearing female animals on the quantity and quality of spermatozoa. The research type carried out was purely experimental with a completely randomized design with 4 treatments, namely control (P0) rearing which contained only 5 male mice, P1 rearing consisting of 3 males and 2 females, and P1 rearing consisting of 3 males and 2 females, P2 consisting of 2 males and 3 females while P3 contained 1 male and 4 female. Each treatment consisted of 6 replications. Animals are kept from 4 weeks old to 10 weeks old. Parameters observed are concentration, motility, and normal morphology of spermatozoa, and data analysis was tested by Kruskall-Wallis Test followed by Duncan’s test. the best spermatozoa compared to other treatments. The results showed that there were significant differences in the quantity and quality of spermatozoa, in the various treatment and maintenance groups, which indicated that the treatment with the composition of 1 male and 4 females had the best quantity and quality of spermatozoa compared to other treatments.